Anomie and strain theories - Gehring, Krista S. (CrimComics, 2019)
Introduces students to Robert Merton's Anomie Theory, which posits that the idea of the American dream is implicated in the social production of crime. It also discusses two extensions of his theory, General Strain Theory and Institutional-Anomie Theory